Low-Latency Error-Prone Optical Networks for Fast Approximate Computation on High-End Datacenters - Koibuchi, Michihiro (2019 24th OptoElectronics and Communications Conference (OECC) and 2019 International Conference on Photonics in Switching and Computing (PSC), 2019)
Cutting-edge application becomes deep learning, big-data processing, the approximate computation for NP-hard problems rather than exact scientific computation on large parallel computers including high-end datacenters and supercomputers. Such emerging applications are typically subject to various kinds of numerical errors, which do not lead to execution failure. The author presents error-prone interconnection networks optimized for these emerging applications. Our interconnection networks provide high bandwidth and low latency at the sacrifice of accuracy. Existing interconnection networks provide almost error-free message transfer by detecting and correcting bit errors, while we do not. Interestingly, some emerging applications work on our error-prone interconnection network with a significant speedup.